ZnS and CuxSy nanoparticles from dithiocarbamate ligands - Mnqiwu, Khumblani (My University, 2017)
Dithiocarbamate ligands and their complexes has been a subject of interest in various fields but they found much interest in medical applications as potential anti-microbial agents. The dithiocarbamate ligands were used to prepare complexes of copper and zinc. All the prepared ligands and complexes were characterized using techniques such as IR and 13CNMR spectroscopy and thermogravimetric analysis (complexes). The data obtained from the spectroscopies was consistent with the coordination of the ligand to the metal ion through the sulfur atoms of the dithiocarbamate or thioureide moiety. The thermal analysis of the prepared complexes gave a final residue of metal sulfide, thus indicating the potential of the prepared complexes as single molecular precursor for the synthesis of metal sulfide nanoparticles. The prepared complexes were then used to synthesize metal sulfide nanoparticles. The nanoparticles were successfully prepared by thermal decomposition of a single-source precursor (dithiocarbamate complexes) in a solution of hexadecylamine (HDA) or tri-n-octylphosphine oxide (TOPO). The investigated parameters were the capping molecule (HDA and TOPO), and capping molecule concentration (3 g and 6 g) to see their effect on the shape and size of the synthesized nanomaterials. The synthesized metal sulfide nanoparticles were characterized using techniques such as UV-vis spectroscopy, photoluminescence spectroscopy, X-ray diffraction analysis and transmission electron microscopy. The absorption study showed some interesting features in the prepared nanomaterials. The first was the red-shifted spectra of the ZnS nanoparticles which was attributed to the impurities and that assumption was further confirmed by the XRD analysis that showed a sulfur impurity and other amorphous peaks. The second was the localized surface plasmon resonances on the copper sulfide nanoparticles that suggested the formation of electron deficient copper sulfide stoichiometry that was further confirmed by XRD analysis that gave hexagonal phase copper sulfide covellite. The TEM images of the prepared nanoparticles showed that the concentration and the capping molecule has an effect on the size and shape of the synthesized nanoparticles. The increase in capping concentration gave a decrease in particle size in most of the prepared nanoparticles, while they were few exceptions. The capping molecule effect showed that most of the nanoparticles prepared from TOPO were spherical in shape and were well dispersed compared to the mixed morphological nanoparticles prepared from HDA. There were also exceptions of the well dispersed HDA-capped nanoparticles.
M.Tech (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Dithiocarbamate ligands, 13CNMR spectroscopy, thermogravimetric analysis, hexadecylamine; Dithiocarbamates.; Nanoparticles.